Penyajian Informasi Untuk Persebaran Lokasi Kerja Alumni STT Terpadu Nurul Fikri Dengan Menggunakan ArcGIS 10.5 - Yekti Wirani; Naila Natalia Aufar; Muh Syaiful Romadhon (Department of Science and Technology Ibrahimy University, 2020)
Geospatial Information System (GIS) is an information system that helps map events on earth to be analyzed with the help of computers. This GIS can make it easier to manage geographic information systems. Based on the results of an interview with the unit manager of the vice-chairman III of STT Terpadu Nurul Fikri, that currently, cannot map and see the visualization of the alumni's work field by the study program. Now, the vice-chairman III unit only can display information data with the help of Microsoft Excel. This study aims to build a Geospatial Information System with the ArcGIS application, making it easier to manage alumni and carry out tracer studies. If this data is available, it will be easier to maintain the relationship between alumni and the STT Terpadu Nurul Fikri. Good alumni data management will also open ample opportunities for collaboration, such as internships, jobs, graduate offers, and information on events and promotions. The results of the evaluation of the information presented were 81.25%, which meant that Deputy Assistant III had agreed with the presentation of data on the distribution of work locations for STT-NF alumni using ArcGIS 10.5. Based on determining the point of work location for STT-NF alumni, it was found that 89% of alumni work in the information technology sector and that their work locations are in the Greater Jakarta area.